Relationship between perceived and actual occupancy rates in urban settings (2016)
Arborists and tree care professionals assess tree risk by considering likelihood of impacting a target, likelihood of failure, and consequence of failure (should a target be impacted). For basic risk assessments, these three factors are typically assessed qualitatively using visual cues, though it is possible to quantify target occupancy (as it relates to the likelihood of impacting a target) using traffic monitoring equipment. For this study, 115 arborists were surveyed to see if their visual assessments of occupancy (based on videos filmed during different seasons and time of day) correlated with the actual measured occupancy counts recorded at four different locations. While there was a significant relationship between visual target occupancy ratings and actual occupancy, ratings were improved when traffic counter data was provided. Additionally, 70% of respondents considered traffic counters a worthwhile investment as they believed they could increase the accuracy of target occupancy assessments. © 2016 Elsevier GmbH